(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This research paper examined school security architecture in an era of digitalization. School security in Nigeria has been a significant concern for several years, particularly due to frequent incidents of kidnappings and attacks by various armed groups. There have been a reported cases of security threats on campuses of Nigerian schools.” A number of Nigerian schools have experienced so many cases of kidnap and abduction of members of the school community. School security architecture refers to the comprehensive framework designed to ensure the safety and security of a school’s students, staff, and property. It encompasses physical, technological, and procedural measures that work together to prevent, detect, and respond to various security threats. Key components of school security architecture typically include, Physical Security, this includes barriers such as fences, gates, secure entry points, surveillance cameras, and alarm systems. Digitalization of school security refers to the integration of digital technologies and systems to enhance the safety and security of educational environments. This process involves leveraging various technological tools to monitor, manage, and respond to potential security threats more effectively. . The goal of digitalizing school security is to create a safer learning environment by leveraging advanced technology to prevent, detect, and respond to potential security threats more effectively and efficiently. It was recommended that implementing digital security in schools comes with several challenges requires a comprehensive approach, Government should make policies that support digitalization in school security, there should be step-by- step guide for schools to implement digital security measures, training and capacity building programs for staff and students on digital security tips and it was concluded that Security is a fundamental and necessary condition for the attainment of institutional goals and must not be compromised.